"Behind the Curtain": Strip Clubs and the Management of Competition for Tips. (February 2018) - Mount, Liz
Ethnographers have amassed a large body of literature on exotic dance and strip clubs. However, this literature contains little information about strip club managers and the work they perform "behind the curtain." This article draws on participant observation in strip clubs and semistructured interviews with managers of strip clubs to explore how managers must work to mitigate the consequences of a payment and staffing structure that exacerbates competition between dancers for tips. Managers are keenly aware of the negative effects of competition between dancers, and they employ motivational tactics to manage the dancers through economic precarity, such as normalizing uncertainty, encouraging self-blame, and using "teamwork" discourses to inculcate a sense of solidarity among dancers and to diffuse the competitive environment in strip clubs. This article reveals how managers strive to normalize and legitimate the precarious work of exotic dancing, contributing to the literatures on exotic dance and tipped employment.